Ensuring national security in the conditions of martial law and state of emergency: theoretical and legal analysis of foreign experience - Gusarov, Serhii; Vasylenko, Viktor; Nosach, Andrii; Korobtsova, Daria (DIXI, 2023)
This article examines, and thoroughly analyzes, the key elements of the current state of national security processes in Ukraine. Also, ways of possible improvement of the state of ensuring the national security of Ukraine in the modern conditions of the active operation of the martial law regime are considered. It is noted that different countries of the world, at their own discretion, tend to interpret the essence and important elements of national security that exist in the world today. In addition, countries have different opportunities to take real action in relation to reforming the situation with their national security. The article focuses on the fact that truly high-quality and dynamic development of the sphere of proper provision of national security occurs in the state only when it is under threat (its state sovereignty, territorial integrity, or other important interests). The example of Israel, the United States and some other countries is not the only one where only after the emergence of this or that danger, the mechanisms and tools to overcome it begin to work in practice. Also, the importance of achieving Ukraine’s full membership in the nato military and political alliance was emphasized. After all, this military and political alliance, which unites about three dozen sovereign states, the majority of which are true liberal democracies with real rule of law and a transparent and effective state system, is recognized as the best example of such a defense alliance in history of humanity and is a good association of states close to Ukraine in spirit. It is indicated that after repelling the Russian invasion, Ukraine should focus all efforts on joining NATO.
Keywords: effective solutions; defense planning; foreign experience; liberal democracy; martial law; military and political alliance; national security; state policy; successful adoption